Editorial Volume 8 Issue 4 - Ciorstan Smark (Australasian Accounting, Business and Finance Journal, 2014)
Financial planning in Australia is in a time of change and challenge. Educational standards and regulation are in flux. There is a strong need to move financial planning into a more esteemed professional position as financial planners are not always considered the safest source of advice for people in Asia and the pacific rim when it comes to investing their much needed retirement funds. This Special Issue on Financial Planning and Financial Instruments brings together articles from financial planning, banking, financial markets and retirement policy.
Keywords: Editorial AABFJ Volume 8 Issue 4